PENANAMAN KARAKTER KEPEMIMPINAN DI PONDOK MODERN DARUSSALAM GONTOR PUTRI MANTINGAN - Fathony Nur Islami; Endah Dwi Utari; Alya Dinia Asyfiqi Masykur; Miftahul Hida Arrohim (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Each pesantren has its own characteristics in the education system that is applied to its students. And as we know, leadership character becomes one of the important things that can be highly suspect in daily life and the implementation of leadership character planting is applied early on in various institutions, as well as in Pondok Darussalam Darussalam Gontor Putri Mantingan. This study focuses on how Pondok Modern Darussalam Gontorr Putri Mantingan instills leadership characteristics in the daily lives of students and their application in society. The results showed that Pondok Gontor Modern Darussalam emphasized on five principles, including: sincerity, simplicity, self-reliance, ukhuwah Islamiyah which fostered a sense of caring and mutual cooperation among Muslims and freedom of thought.